Surgical Management of Secondary Uterine Inertia in Two Bitches - Raval, RJ; Vala, KB; Parmar, KH; Talekar, SH (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Primary or secondary uterine inertia is due to lack of normal physiological uterine contraction during or after parturition. Secondary uterine inertia is commonly observed in bovine, however, it is comparatively less reported in canine